THE EFFECTS OF SYZYGIUM AROMATICUM-DERIVED TRITERPENES ON GASTROINTESTINAL GHRELIN EXPRESSION IN STREPTOZOTOCIN-INDUCED DIABETIC RATS - Luvuno, Mluleki; Prosperity Mbongwa, Hlengiwe; Khathi, Andile (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Diabetic polyphagia has been associated with elevated plasma ghrelin levels in experimental type 1 diabetes. This increase in food consumption contributes to chronic hyperglycaemia in diabetes thus contributing to the development of micro- and macrovascular complications.We have reported that plant-derived oleanolic acid (OA) and maslinic acid (MA) reduce blood glucose levels, in part, through the inhibition of intestinal carbohydrate hydrolyzing enzymes and glucose transporters. However, their effects on food intake and plasma ghrelin concentrations are unclear. Accordingly, we investigated the effects of these triterpenes on food intake and ghrelin expression in streptozotocin-induced diabetic rats. Material: The effects of OA and MA on blood glucose concentration; food and water intake were monitored over five weeks after which plasma ghrelin concentrations were measured. Additionally, the expression of ghrelin in the various sections of the GIT was determined using Western blot analysis. Results: Ghrelin concentrations in untreated STZ-induced diabetic rats were significantly higher in comparison to the non-diabetic control. Interestingly, the administration of OA and MA reduced food intake, blood glucose levels and plasma ghrelin levels in STZinduced diabetic rats. This was further complemented by significant reductions in the gastrointestinal expression of ghrelin suggesting that the anti-diabetic properties of these triterpenes are mediated, in part, through the reduction of food intake and the modulation of ghrelin expression. Conclusion: The findings of the study suggest that the control of food intake through the reduction of ghrelin expression by plantderived OA and MA may constitute an avenue of glycaemic control in diabetes mellitus.